The gut microbiota as an early predictor of COVID-19 severity - Fabbrini, Marco; D’Amico, Federica; van der Gun, Bernardina T. F.; Barone, Monica; Conti, Gabriele; Roggiani, Sara; Wold, Karin I.; Vincenti-Gonzalez, María F.; de Boer, Gerolf C.; Veloo, Alida C. M.; van der Meer, Margriet; Righi, Elda; et al. (mSphere, 2024)
Efficient patient triage for COVID-19 is vital to manage healthcare resources effectively. This study underscores the potential of gut microbiota (GM) composition as an early biomarker for COVID-19 severity. By analyzing GM samples from 315 patients, significant correlations between microbial diversity and disease severity were observed. Notably, a convolutional neural network classifier was developed, achieving an 81.5% accuracy in predicting disease severity based on GM composition at disease onset. These findings suggest that GM profiling could enhance early triage processes, offering a novel approach to optimizing patient management during the pandemic.